Accommodating muon (g − 2) and leptogenesis in a scotogenic model - A. Alvarez; A. Banik; R. Cepedello; B. Herrmann; W. Porod; M. Sarazin; M. Schnelke (Journal of High Energy Physics, 2023)
Abstract We present a detailed study of a scotogenic model accommodating dark matter, neutrino masses and the anomalous magnetic moment of the muon while being consistent with the existing constraints on flavour violating decays of the leptons. Moreover, this model offers the possibility to explain the baryon asymmetry of the Universe via leptogenesis. We determine the viable regions of the model’s parameter space in view of dark matter and flavour constraints using a Markov Chain Monte Carlo setup combined with a particular procedure to accommodate neutrino masses and the anomalous magnetic moment of the muon at the same time. We also discuss briefly the resulting collider phenomenology.